Influence of immunosuppression on the progression of experimental periodontitis and on healthy periodontal tissue: A rat in vivo study - Juliano Milanezi de Almeida; Henrique Rinaldi Matheus; Luiz Guilherme Fiorin; Elisa Mara Abreu Furquim; David Jonathan Rodrigues Gusman (Tabriz University of Medical Sciences, 2021)
Background. The potent anti-inflammatory and immunosuppressive properties of glucocorticoids (GCs) might influence the progression of some disorders, such as periodontitis. Hence, this study aimed to investigate the influence of dexamethasone (DEX) on the alveolar bone loss (ABL) of healthy and periodontally compromised molars in rats. Methods. Thirty male rats were randomly assigned to two groups: physiological saline solution (PSS) and DEX. The animals received subcutaneous injections of either 0.5 mL of PSS) (group PSS) or 2 mg/kg of DEX (group DEX) from one day before experimental periodontitis (EP) induction until euthanasia. EP was induced through ligature placement around the mandibular lower first molars at day 0. Contralateral molars remained unligated. Ten animals per period were euthanized on days 3, 7, and 14. Morphometric analysis was performed to access the ABL. Data were statistically analyzed with ANOVA followed by post hoc Tukey tests (P≤0.05). Results. Higher ABL was observed in both groups on days 7 and 14 than on day 3 (P≤0.05). Concerning periodontitis, higher ABL was observed in group DEX on days 3, 7, and 14 days than group PSS at the same time intervals (P≤0.05). Also, even in the contralateral unligated molars, group DEX exhibited higher ABL on days 3, 7, and 14 days than group PSS at the same time intervals (P≤0.05). Conclusions. Collectively, it can be concluded that DEX aggravates EP and induces spontaneous ABL in the healthy periodontium.